Differences in MAT gene distribution and expression between Rhynchosporium species on grasses - King, K.M.; West, J.S.; Fitt, B.D.L.; Dyer, Paul S. (Wiley, 2015)
Leaf blotch is a globally important disease of barley crops and other grasses that is caused by at least five host-specialized species in the fungal genus Rhynchosporium. The pathogen R. commune (specialized to barley, brome-grass and Italian ryegrass) has long been considered to reproduce only by asexual means, but there has been accumulating evidence for recombination and gene flow from population genetic studies and the detection of complementary MAT1-1 and MAT1-2 isolates in a c. 1:1 ratio in the field. Here, it is demonstrated that 28 isolates of the closely related species R. agropyri (on couch-grass) and R. secalis (on rye and triticale), collected from Europe, were also either of MAT1-1 or MAT1-2 genotype and that the distribution of mating types did not deviate significantly from a 1:1 ratio. Evidence is then provided for MAT1-1-1 and MAT1-2-1 gene expression during mycelial growth for all three species. By contrast, 27 isolates of the more distantly related R. orthosporum (on cocksfoot) and R. lolii (on Italian and perennial ryegrasses) from Europe were exclusively of the MAT1-1 genotype, and expression of the MAT1-1-1 gene could not be detected during mycelial growth. These data suggest that cryptic sexual cycles are more likely to exist for R. commune, R. agropyri and R. secalis than for either R. orthosporum or R. lolii. A phylogenetic analysis of partial MAT1-1 idiomorph sequences resolved these five species into two distinct groups (R. commune, R. agropyri and R. secalis versus R. orthosporum and R. lolii) but provided only limited resolution within each group.